2020
DOI: 10.1111/cns.13549
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Parkinson's disease: A systematic review and meta‐analysis of comparative studies

Abstract: Background Studies regarding the impact of Parkinson's disease (PD) on quality of life (QOL) have reported conflicting results, and the underlying QOL domains require further study. In order to understand the association between PD and QOL, we conducted this meta‐analysis to systematically compare QOL between PD patients and healthy controls. Method The PubMed, PsycINFO, EMBASE, and Web of Science databases were systematically searched. Data were analyzed using the random‐effects model. Results Twenty studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 79 publications
3
83
0
5
Order By: Relevance
“…QoL is considered a vital outcome indicator in patients with PD [ 29 ]. A broad list of motor and non-motor symptoms was shown to be important contributors to QoL in patients with PD [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…QoL is considered a vital outcome indicator in patients with PD [ 29 ]. A broad list of motor and non-motor symptoms was shown to be important contributors to QoL in patients with PD [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This concomitant depressive symptomatology is ultimately crucial for explaining why nonadherence and decreased medication knowledge contribute to a poorer HRQoL, which is in turn associated with increased nonadherent behavior, such as intentional nonadherence (i.e., changing medications without consulting the physician). Depression has been shown to strongly influence HRQoL [39,40]; however, the exact effect of depression is not yet fully understood, especially with regard to the complex association among worse health status, health literacy, and depression [41]. A previous study reported that, while depressed patients showed significantly worse health status, low health literacy itself did not predict depressive symptomology [42].…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a chronic, progressive neurodegenerative disease that severely affects the HRQoL of patients compared to healthy controls [ 6 ]. The correlates of poor HRQoL in PD patients are multifactorial and include demographics (such as age and gender), PD clinical characteristics (such as severity of motor and non-motor symptoms, PD subtypes, disease duration), adverse effects of treatment, comorbid conditions, and psychosocial function [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The correlates of poor HRQoL in PD patients are multifactorial and include demographics (such as age and gender), PD clinical characteristics (such as severity of motor and non-motor symptoms, PD subtypes, disease duration), adverse effects of treatment, comorbid conditions, and psychosocial function [ 7 9 ]. Both generic and PD-specific HRQoL tools have been used in PD patients [ 3 , 6 , 10 – 13 ]. Among the currently available PD-specific HRQoL tools, the Parkinson’s disease questionnaire-39 item (PDQ-39) that contains 39 items that are grouped under 8 domains, and its shorter version PDQ-8 that contains 8 items, each representing a domain of the PDQ-39 are more widely used [ 10 , 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation